Early detection and differential serodiagnosis of Mycoplasma hyorhinis and Mycoplasma hyosynoviae infections under experimental conditions - Giménez-Lirola, Luis G.; Meiroz-De-Souza-Almeida, Henrique [UNESP]; Magtoto, Ronaldo L.; McDaniel, Aric J.; Merodio, Maria M.; Matias Ferreyra, Franco S.; Poonsuk, Korakrit; Gatto, Igor R.H. [UNESP]; Baum, David H.; Ross, Richard F.; Arruda, Paulo H.E.; Schwartz, Kent J.; et al. (Public Library of Science (PLoS), 2019)
Mycoplasma hyorhinis (MHR) and Mycoplasma hyosynoviae (MHS) are common opportunistic pathogens in the upper respiratory tract and tonsils of swine. The identification of the specific species involved in clinical cases using conventional diagnostic methods is challenging. Therefore, a recombinant chimeric polypeptide based on the seven known variable lipoproteins (A-G) specific of MHR and a cocktail of surface proteins detergent-extracted from MHS cultures were generated and their suitability as antemortem biomarkers for serodiagnosis of MHR- and MHS-infection were evaluated by ELISA. M. hyorhinis and MHS ELISA performance, evaluated using serum samples collected over a 56-day observation period from pigs inoculated with MHR, MHS, M. hyopneumoniae, M. flocculare, or Friis medium, varied by assay, targeted antibody isotype, and cutoffs. The progressions of MHR and MHS clinical diseases were evaluated in relation to the kinetics of the isotype-specific antibody response in serum and bacterial shedding in oral fluids during the observation period. In pigs inoculated with MHR, bacterial DNA was detected in one or more of the 5 pens at all sampling points throughout the study, IgA was first detected at DPI 7, one week before the first clinical signs, with both IgA and IgG detected in all samples collected after DPI 14. The peak of MHS shedding (DPI 8) coincided with the onset of the clinical signs, with both IgA and IgG detected in all serum samples collected ≥ DPI 14. This study demonstrated, under experimental conditions, that both ELISAs were suitable for early detection of specific antibodies against MHR or MHS. The diagnostic performance of the MHR and MHS ELISAs varied depending on the selected cutoff and the antibody isotype evaluated. The high diagnostic and analytical specificity of the ELISAs was particularly remarkable. This study also provides insights into the infection dynamics of MHR-associated disease and MHS-associated arthritis not previously described.